Malawi : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The Malawi Growth and Development Strategy II (MGDS-II) is a poverty reduction strategy for the period 2006-11, which is aimed at fulfilling Malawi's future developmental aspiration-Vision 2020. The strategy identifies broad thematic areas and key priority areas to bring about sustained economic growth. A striking feature of this strategy is that the various governmental organizations, private sector, and general public are equal stakeholders. However, successful implementation of MGDS-II will largely depend on sound macroeconomic management and a stable political environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet